AI179 single-chain antibody recognizes the Myc tag by Western blotting - Keszei, Zsofia; Picard, Didier (Antibody Reports, 2019)
The recombinant antibody AI179 against the Myc tag detects a Myc-tagged protein exogenously expressed in human cells by Western blotting.